Prevalence of Polymorphism and Post-Training Expression of ACTN3 (R/X) and ACE (I/D) Genes in CrossFit Athletes - Güereca Arvizuo, Jaime (2023)
Abstract: Background: CrossFit is known as a functional fitness training high-intensity exercise to improve physical performance. The most studied polymorphisms are the ACTN3 R577X gene, known for speed, power, and strength, and ACE I/D, related to endurance and strength. The present investigation analyzed the effects of training on ACTN3 and ACE gene expression in CrossFit athletes for 12 weeks. Methods: the studies included 18 athletes from the Rx category, where ACTN3 (RR, RX, XX) and ACE (II, ID, DD) characterization of genotypes and tests of maximum strength (NSCA), power (T-Force), and aerobic endurance (Course Navette) were performed. The technique used was the reverse transcriptionquantitative PCR real-time polymerase chain reaction (RT-qPCR) for the relative expression analysis. Results: the relative quantification (RQ) values for the ACTN3 gene increased their levels 2.3 times (p = 0.035), and for ACE, they increased 3.0 times (p = 0.049). Conclusions: there is an overexpression of the ACTN3 and ACE genes due to the effect of training for 12 weeks. Additionally, the correlation of the expression of the ACTN3 (p = 0.040) and ACE (p = 0.030) genes with power was verified.